End of Meeting Report - ISPC 15 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
The fifteenth meeting of the ISPC was held from 04-05 April 2017 in Rome, Italy View presentations here (https://www.slideshare.net/ISPC-CGIAR/tag/ISPC15)